Seasonal Trends, Profiles, and Exposure Risk of PM2.5-bound Bisphenol Analogs in Ambient Outdoor Air: A Study in Shanghai, China - Janvier Munyaneza; Fahim A. Qaraah; Qilong Jia; Hanting Cheng; Huajun Zhen; Guangli Xiu (Aerosol and Air Quality Research)
Abstract Fine particulate matter (PM2.5) possesses a larger surface area, which enables hazardous chemicals to adsorb. The particle can lodge deep in the lungs and bronchi of humans, causing diverse cardiovascular and respiratory diseases. PM2.5 exposure has significant socioeconomic repercussions as well as an increased risk of mortality. Some features of PM2.5 components have yet to be fully comprehended. PM2.5-bound bisphenols (BPs), which mostly originate from the incineration of plastic waste, haven’t been profoundly documented, and some of their patterns are not explicitly understood. Between July 2019 and November 2020, the measurement of bisphenol A (BPA) and its 5 analogs was undertaken using outdoor PM2.5 samples from Shanghai. Three BPs (BPA, bisphenol F (BPF) and bisphenol S (BPS)) were frequently identified (88%; 82% and 75% respectively), with concentration ranges (mean; median) of 0.051 to 7.52 ng m−3 (2.75 ng m−3; 2.40 ng m−3), 0.014 to 6.32 ng m−3 (2.44 ng m−3; 2.007 ng m−3), and 0.005 to 4.61 ng m−3 (0.29 ng m−3; 0.031 ng m−3) respectively. The highest average concentrations (BPA: 3.47 ng m−3; BPF: 2.46 ng m−3; BPS: 0.58 ng m−3, and bisphenol AF (BPAF): 1.14 ng m−3) were found within samples collected in winter periods. A strong and positive correlation was denoted between the concentrations of BPA and bisphenol B (BPB) (r = 0.719, p < 0.05), when an inversely significant correlation was noticed between BPA and BPF (r = –0.264, p < 0.05). The estimated daily intakes (EDIs) varied from 7.76 × 10−4 to 3.51 ng kg BWt−1 Day−1. The hazard quotient (HQ) which ranged from 8.61 × 10−9 to 7.02 × 10−5 with BPA determined as the major contributor (97.08% for ∑HQ) wasn’t detrimental to the health of Shanghainese. Considering EDIs and HQs data, children were more subjected to health effects associated with the inhalation of BPs than adults. We came up with confirmations that industrial and anthropogenic activities are the major contributors to the load of airborne BPs in Shanghai. We also noticed that meteorological parameters aren’t the sole deterministic factors influencing the seasonal profiles of BPs.